(3QjGV GdeSGFd aj HjGf CMcGe GdTQY HGdOdGFds - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs
(3ChdgG (B:s
(3cJGH GdehGQjK gh CYe ef GdaQGFV eWdbG Ef CQjO HgG GdeaQhV HGdJaUjd hEf CQjO HgG eG jYe GdELeGd cEQK Chdj GdCQMGe agh HeYfi hef Ke cGf GdJYHjQ HeG gfG Chdi ef GdJYHjQ HGdaQGFV hGdCUd ajg HYO GdELeGY GdcJGH hGdSfI (B...s
(3BNQgG (B:s
... (3VQH GdcShQ gh bSeGf HGYJHGQ hbhY GdcSQ aj CMO GdWQajf Ch cdjgeG dcfG fbJUQ gfG Ydi GdChd dchfg GdCcKQ hbhYG aj gPG GdHGH eY RjGOI UYhHJg aj GdbSe GdBNQ (B...(3hgPG BNQ eG LQi Hg GdYdes
(3JGQjN JCdag (B: (3QeVGf (B1255 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3EjVGM Gdecfhf (B1\ 603s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis